Interactive effects of MnO(2), organic matter and pH on abiotic formation of N(2)O from hydroxylamine in artificial soil mixtures - Liu, Shurong (Sci Rep, 2017)
Abiotic conversion of the reactive nitrification intermediate hydroxylamine (NH(2)OH) to nitrous oxide (N(2)O) is a possible mechanism of N(2)O formation during nitrification. Previous research has demonstrated that manganese dioxide (MnO(2)) and organic matter (OM) content of soil as well as soil pH are important control variables of N(2)O formation in the soil. But until now, their combined effect on abiotic N(2)O formation from NH(2)OH has not been quantified. Here, we present results from a full-factorial experiment with artificial soil mixtures at five different levels of pH, MnO(2) and OM, respectively, and quantified the interactive effects of the three variables on the NH(2)OH-to-N(2)O conversion ratio (R(NH2OH-to-N2O)). Furthermore, the effect of OM quality on R(NH2OH-to-N2O) was determined by the addition of four different organic materials with different C/N ratios to the artificial soil mixtures. The experiments revealed a strong interactive effect of soil pH, MnO(2) and OM on R(NH2OH-to-N2O). In general, increasing MnO(2) and decreasing pH increased R(NH2OH-to-N2O), while increasing OM content was associated with a decrease in R(NH2OH-to-N2O). Organic matter quality also affected R(NH2OH-to-N2O). However, this effect was not a function of C/N ratio, but was rather related to differences in the dominating functional groups between the different organic materials.